Cutting-edge issues in Business Ethics Continental Challenges to Tradition and Practice - Painter-Morland, Mollie; Werhane, Patricia; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
This volume is one of the very few publications dedicated to the challenges that Continental philosophy poses to the field of Business Ethics. The authors want to draw attention to the work of Continental philosophers who have been relegated to the fringes of Business Ethics scholarship, and present some critical perspectives that have been ignored within Business Ethics practice. As such, this volume provides a critique of many of the assumptions that underpin traditional approaches to Business Ethics, and urges its readership to rethink moral agency and epistemology, as well as Business Ethics pedagogy.
Are We Victims of Circumstances? Hegel and Jean-Paul Sartre on Corporate Responsibility and Bad Faith -- (3z(BIt$1 (Bs Business; We$1 (Bre Soldiers(3y(B: The Sopranos, Liberal Business Ethics, and this American Thing of Ours -- Redefining Accountability as Relational Responsiveness -- Hegel on the Place of Corporations Within Ethical Life -- Abjection, Ambiguity, and Female Sweatshop Workers: Is Alienated Labor Really an Ethical Problem? -- The Grameen Bank and Capitalist Challenges -- Building an Ethics of Visual Representation: Contesting Epistemic Closure in Marketing Communication -- Of Dice and Men -- Business, Ethics and the Hope of Society in Hannah Arendt: The Notion of Responsible Business Entrepreneurship -- Continental Philosophy: A Grounded Theory Approach and the Emergence of Convenient and Inconvenient Ethics -- Contribution Towards a Phenomenological Approach to Business Ethics -- Mental Models, Moral Imagination and System Thinking in the Age of Globalization: A Post-Colonial Proposal -- Business Ethics Beyond the Moral Imagination: A Response to Richard Rorty -- An Arendtian Approach to Business Ethics -- A Marxist in the Business Ethics Classroom.s
Keywords: Business; Business ethics; Ethics; Economic theory; Business and Management; Business Ethics; Ethics; Economic Theory/Quantitative Economics/Mathematical Methods; Electronic books